AWARENESS OF CTA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
George Ekukole, D Senchim, Dakar, Senegal: 'I deplore the fact that some of our graduate students are unaware of the roleof CTA and I think that some of our senior scientists/researchers are to blame for failing to pass on this vital...